Majewski osteodysplastic primordial dwarfism type II (MOPD-II): A rare case report - Sobhan, Rezwana; Khan, Hafsa Hasan; Pathan, Md Faruque; Afsana, Faria; Amin, Feroz (BIRDEM Medical Journal, 2019)
Majewski osteodysplastic primordial dwarfism type II (MOPD-II) is a rare syndrome characterized by the presence of intrauterine growth restriction, post-natal growth deficiency and microcephaly. Individuals affected by this disease present at an adult height of less than 100 cm, a post-pubertal head circumference of 40 cm or less, mild mental retardation, an outgoing personality and skeletal dysplasia, renal, hematopoietic abnormalities, cerebral vascular anomalies (aneurysm and Moyamoya disease). It is an autosomal recessive syndrome with equal gender occurrence involving the DNA damage-response PCNT gene. Here is an interesting case report of a 15-year-old boy, who presented with growth failure since age of one year, noticed by his parents with history of low birth weight (1.5 kg), delayed developmental milestones, microcephaly, low IQ and difficulty in walking due to short left leg. He had bird like head with beaked nose, crowding of teeth and malocclusion. Complete blood picture and hormonal analysis are within normal range except low growth hormone, typical radiographic features including severe scoliosis and dislocation of hip correlated with MOPD-II. Growth hormone therapy was thought to be ineffective. Genetic counselling is important to prevent the occurrence of MOPD-II. Birdem Med J 2019; 9(3): 254-256